THE PROTECTIVE EFFICACY OF MATERNALLY DERIVED ANTIBODIES AGAINST INFECTIOUS BURSAL DISEASE VIRUS IN BROILER CHICKS - M. A, Ahmed; A. S 2, Aii, (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to assess the protective potentials and decaying pattern of the maternally derived antibodies (MDAs) in broiler chicks against infectious bursal disease virus (IBDV). For this purpose, twenty five unvaccinated chicks were used. These chicks were hatched from chickens vaccinated by the live IBDV vaccine containing the chick-embryo propagated, D78 intermediate strain of the virus. The enzyme-linked immunosorbent assay (ELISA) was used to determine the antibody (Ab) levels in the chicks sera at various points of time. The study revealed that the MDAs against IBDV in chicks persisted up to the sixth week of chicks age. However, the protective level of these antibodies expired by the fourth week.. Based on these data, we suggest that, for appropriate vaccination day, the level of MDAs must be evaluated while the chicks are growing at 14 -20 days of age and probably one week later.